LEGAL GOVERNANCE OF ROHINGYA REFUGEE AFFAIRS IN ACEH: A CONSTITUTIONAL PERSPECTIVE - Hakim, Adib; Arini Nur Annisa (JURNAL SULTAN: Riset Hukum Tata Negara, 2024)
This study aims to analyze the implementation of governance for refugees who come to Indonesia, in this case, Rohingya refugees. The arrival of Rohingya refugees in Indonesia has introduced complexity to the regional response, posing challenges for the Indonesian government in upholding humanitarian standards, ensuring proper living conditions, and managing public sentiments. This research employs a juridical-normative approach to analyze the legal norms governing the Indonesian government's policies on Rohingya refugees, focusing on instruments like Presidential Regulation 125/2016. By examining legal regulations and sources, this study identifies and evaluates the legal implications of implemented policies, assessing their alignment with prevailing legal principles. The international legal framework, including the 1951 UN Refugee Convention and the 1967 Protocol, alongside Indonesia's comprehensive immigration legal framework (Law Number 6 of 2011), is crucial. Despite these legal foundations, challenges persist in handling Rohingya refugees in Aceh, highlighting a disconnect between the legal framework and on-the-ground realities, notably in the face of local community rejection.